Tawaran Solusi LGBT al-Husain al-Bashri al-Mu’tazily Dalamal-Mu’tamad - Aldomi Putra (LP2M Universitas PTIQ Jakarta, 2018)
This paper addresses LGBT case resolahe focus of the LGBT is that the issue has been quite controversial today in Indonesia, due to the enormous lesbian, gay and transgender community in many major cities in Indonesia. They have moved to demand their rights to be respected, and are even championing their relationship to legitimacy by marriage laws. How to understand the qaum Lūṭstory which is the forerunner of LGBT by al-Husain al-Bashri al-Mu’tazilî in the book al-Mu’tamād with the theory of al-’Af’aland al-Qiyās al-Syar’I, so the LGBT actors are excluded from al-’Af’al al-Qabîh who is condemned to punishment for those who commit adultery, because the illah or the reason isn’t the same as fahisha(same sex sexual conduct).